Ordering objects via attribute preferences - Cabrera, Inma P.; Ojeda-Aciego, Manuel; Pocs, Jozef (My University, 2014)
We apply recent results on the construction of suitable orderings for the existence of right adjoint to the analysis of the following problem: given a preference ordering on the set of attributes of a given context, we seek an induced preference among the objects which is compatible with the information provided by the context.
Keywords: Análisis matemático; Formal Concept Analysis